Self-Reported Prevalence & Associated Factors for Occurrence of Recurrent Aphthous Stomatitis (RAS) in Undergraduate Medical & Dental Students - Afridi, Saira; Kundi, Jawad Ahmad; Hayat, Faisal (Journal of Gandhara Medical and Dental Science, 2014)
Background: Recurrent aphthous stomatitis (RAS) is the most common painful oral lesions that occur frequently in young adults; however the etiology still remains unknown. The present study was conducted to explore the prevalence of RAS in undergraduate medical & dental students as these are the group who are in their early adulthood and are prone to stress during studies . Materials and Methods: This was a cross-sectional survey carried out in Gandhara University. Two hundred students of MBBS & BDS participated in the questionnaire survey. Interview was done through a close-ended questionnaire to report the prevalence of RAS, the associated history, clinical features & preferred treatment. Results: Prevalence of RAS was found to be 87.5% in the study population. Most common site was lower lip where 20% people have ever experienced oral ulcer. Most of the participants (46%) tried topical gels and 55% found the treatment effective. Majority was not sure which medication they used. Approximately half (48%) of the students associated the ulcer onset with their psychological stress. Conclusion: The prevalence of RAS was found to be alarming (85.7%) among medical and dental students of Gandhara University. The most common associated factors as experienced and reported by the students were found to be family predisposition and psychological stress.